PENGARUH KEBIJAKAN MONETER TERHADAP INFLASI DI INDONESIA SELAMA PANDEMI COVID-19 - I Gusti Ayu Made Agung Mas Andriani Pratiwi; Yoga, I Made Sedana (Universitas Tabanan, 2023)
The COVID-19 pandemic that has affected Indonesia has also played a role in the development of Indonesia's economy and is feared to trigger inflation. Various policies have been implemented, including monetary policies involving interest rate determination by Bank Indonesia and regulating the circulation of money in society. The aim of this research is to analyze the influence of interest rates and the amount of money in circulation on inflation and to examine the role of the money supply in mediating the influence of interest rates on inflation in Indonesia. This research uses secondary data obtained from the Central Bureau of Statistics (BPS). Data processing tools used in this research include Microsoft Excel and path analysis. The findings of this study are as follows: interest rates have a negative but non-significant impact on inflation in Indonesia during the COVID-19 pandemic, interest rates have a positive and significant impact on inflation in Indonesia during the COVID-19 pandemic, the amount of money in circulation has a positive and significant impact on inflation in Indonesia during the COVID-19 pandemic, and the amount of money in circulation does not mediate the influence of interest rates on inflation in Indonesia during the COVID-19 pandemic.